Elementary Operators and Their Applications 3rd International Workshop held at Queen's University Belfast, 14-17 April 2009 - Curto, Raul; Mathieu, Martin (Operator Theory: Advances and Applications, 2011)
This volume contains solicited articles by speakers at the workshop ranging from expository surveys to original research papers, each of which carefully refereed. They all bear witness to the very rich mathematics that is connected with the study of elementary operators, may it be multivariable spectral theory, the invariant subspace problem or tensor products of C*-algebras. Contributors: N. Boudi D. Kitson B. Magajna M. Mathieu P. Rosenthal V.S. Shulman R.M. Timoney Yu.V. Turovskii L. Turowska.